Clinico-epidemiological evaluation of patients with sinonasal masses attending a tertiary care hospital in Jharkhand: a three year retrospective study - Pandey, Ranbir Kumar; Kumar, Dheeraj; Shrivastava, Nisha; Kumar, Nishant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
Background: Nasal cavity may contain wide variety of masses within by which this organ differs from the rest of the body. Benign nasal and paranasal sinus masses are commonly encountered in clinical practice. The purpose of this study was to classify various types of sinonasal masses and characterize their clinico-epidemiological profile in a tertiary care hospital of Jharkhand. The objectives of the study was to evaluate the clinico-epidemiological profile of nasal masses in patients attending ear, nose, throat and head and neck surgery (ENT & HNS) OPD of Rajendra Institute of Medical Sciences (RIMS), Ranchi from January 2013 to December 2015) and to classify the nasal masses according to their percentage of occurrence. Methods: This retrospective study was designed for evaluation of clinico-epidemiological data collected from admission register of ENT Dept. RIMS, Ranchi during the period of 2013 to 2015. Total sample size for this period was 240. Templates were generated in MS Excel sheets and analysis was done using SSPS software. Results: With the three year data analysis of 240 patients, we came up with the result that nasal masses were more common in age group of <20 years (52%), occurred more in males (68.4%), most of the patients were tribals (72.9%), mostly from rural areas (60%), and maximum of them were diagnosed as antrochoanal polyps (37.9%). The most common presenting complain was nasal obstruction (85.8%), followed by nasal discharge (52.9%). Conclusions: Antrochoanal polyp is the most common type of nasal masses presenting mostly in tribal males from rural areas of Jharkhand, presenting with nasal obstruction.